Response of Cedrela odorata L. to several mycorrhizal inoculants from two tropical ecosystems - Méndez-Cortéz, Heriberto; Marmolejo-Monsiváis, José G.; Cantú-Ayala, César; Olalde-Portugal, Víctor; Estrada-Castillón, Eduardo; Posadas-Leal, César (Instituto de Ecología, A.C., 2013)
This study shows the effect of some inoculants of the arbuscular mycorrhizal fungi (AMF) on theinitial development Cedrela odorata L; for this, a bioassay was conducted with different inoculum sourcesof two tropical forests where this species is distributed in Veracruz state. Four treatments were applied: T1,direct inoculation with a spore consortium; T2: inoculation with mycorrhizal roots from field; T3: withoutinoculation; T4: native soil not sterile. (T1, T2 and T3 in native sterilized soil). The analyzed variables weredry aerial and root biomass, height, diameter, leaflets number, spores number, and colonization percentage.Statistical analysis showed significant differences between inoculants from medium tropical forest(MTF), where T4 was the best results followed by T2, while T3 observed the lowest values. Although theinoculants of high tropical forest (HTF), do not have statistical significance, the results were similar to thosein the MTF. These results showed a good micorrhizal relationship between these fungi and C. odorata; for this reason, it is recommended to reproduce this fungus to use in plants production in order to obtain plants best adapted to natural conditions.